The role of fetal magnetic resonance imaging in high risk monochorionic diamniotic pregnancy. (18th April 2012) - Taylor-Clarke, M; Allsop, J; McGuinness, A; Gardiner, HM; Wimalasundera, RC; Rutherford, MA
Abstract : Monochorionic twins are at increased risk of congenital and antenatally acquired brain anomalies, particularly in the presence of twin-twin transfusion syndrome (TTTS) or single intrauterine death (sIUD). This study demonstrates the role of fetal MRI in diagnosing brain abnormalities in high risk MCDA pregnancies. Fetal MR and ultrasound findings were compared in 93 consecutive high risk MCDA pregnancies (142 fetuses) referred to our unit between 2007-2011; 26 twin pairs post fetoscopic laser ablation (FLAP) for TTTS, 13 twin pairs with structural abnormalities detected on ultrasound and 44 survivors of sIUD (13 post FLAP, 19 fetocides with radiofrequency ablation, 12 spontaneous). MR scans performed according to our local fetal protocol include T1 and T2 weighted images. Ultrasound was performed at the referring unit a median of 8 days before MRI. MR and ultrasound findings were concordant for normal findings in 69% of pregnancies and for abnormal findings in 10%. Findings were discordant in the remaining 21% (3% MR findings less severe than US, 11% abnormalities on MRI with normal ultrasound, 7% additional abnormalities seen on MRI). New MR findings occurred in all referral groups (22% TTTS twin pairs, 14% sIUD singletons and 31% twin pairs with structural abnormalities) leading to increased surveillance, earlier intervention or altered postnatal management. Fetal MRI confirms abnormality or detects new findings in 1 in 3 high risk MCDA pregnancies. Fetal MRI provides parents and clinicians with important additional information that impacts future management and should be routine in all high risk MCDA pregnancies.